Comparison of Scour Properties of Classical and Trapezoidal Labyrinth Weirs - Ikinciogullari, Erdinc; Emiroglu, Muhammet Emin; Aydin, Mehmet Cihan (Springer Heidelberg, 2022)
Free overfall structures might affect the structural safety of weirs. Thus, it is essential to minimize local scour in the downstream pool to ensure structural safety. In the present study, triangular, trapezoidal, and labyrinth weirs were analyzed numerically for free overfall with the Computational Fluid Dynamics method to estimate local scour depths. The finite-volume approach was employed to solve the RANS equations by using Flow-3D software. For turbulence closure, the standard k-e turbulence model was preferred, which is widely used in the literature with certain confidence especially in open channel problems. The numerical results were tested with some experimental observations, and a reasonable agreement was achieved between numerical and physical model results. The findings also indicated that the local scour at the labyrinth weir downstream is lower than that of the classical weirs, while the horizontal distance of maximum scour depth in the labyrinth weir is lower than that in the classical ones.
Keywords: Local scour; CFD; Flow3D; Free overfall weir; Dam; Spillway; Labyrinth weir